Diurnal fluctuation of ocular blood flow parameters in patients with primary open-angle glaucoma and healthy subjects. Issue 4 (24th November 2008) - Pemp, B; Georgopoulos, M; Vass, C; Fuchsjäger-Mayrl, G; Luksch, A; Rainer, G; Schmetterer, L
Abstract : Background/aims: To investigate the fluctuations of ocular blood flow parameters over 13 h in patients with primary open-angle glaucoma (POAG) and in healthy eyes, and to relate these fluctuations with variations in intraocular pressure (IOP) and mean ocular perfusion pressure (OPP). Methods: 15 patients with POAG and 15 control subjects were included. Measurements of systemic blood pressure (SBP), fundus pulsation amplitude (FPA), choroidal blood flow (CHBF), optic nerve head blood flow (ONHBF) and IOP were performed at 08:00, 12:00, 17:00 and 21:00. OPP was calculated from IOP and SBP. The coefficient of variation (CV) was calculated for all individual parameters to assess their variability. Results: The time response of the ocular haemodynamic variables was not different between the groups. Most of the outcome variables showed significantly larger fluctuations in patients with POAG compared with healthy controls (CV: FPA: 0.085 (SD 0.033) vs 0.054 (0.029), p = 0.012; CHBF: 0.082 (0.030) vs 0.052 (0.023), p = 0.005; ONHBF: 0.086 (0.044) vs 0.059 (0.032), p = 0.063). These changes were not associated with OPP or IOP. Changes over time correlated among the different ocular haemodynamic outcome measures in patients with POAG (r = 0.678, r = 0.557, r = 0.545; p<0.04) but not in the control subjects (r = 0.336, r = −0.227, r = −0.130; p>0.22). Conclusion: Patients with POAG show a larger diurnal fluctuation of ocular blood flow parameters. These fluctuations appear not to be related to a higher statistical error of the applied measurement techniques in POAG patients. These data support the hypothesis that POAG is associated with vascular dysregulation.